A two-surface plasticity model for clay; numerical implementation and applications to large deformation coupled problems of geomechanics. (November 2021) - Sabetamal, Hassan; Salgado, Rodrigo; Carter, John P; Sheng, Daichao
Abstract: This paper presents numerical treatments of elastoplasticity relations for a previously developed critical state two-surface plasticity model and its implementation into a bespoke finite element code as well as the commercial software Abaqus via the user defined subroutine, UMAT. The model is implemented with an efficient integration scheme based on the explicit modified Euler scheme with automatic substepping and error control. Validation of the implemented model is assessed through simulation of several laboratory tests comprising a variety of initial states and loading conditions followed by a study on the accuracy and efficiency of the integration scheme. Subsequently, the model is employed to analyse some sophisticated boundary value problems involving finite deformations, inertia effects, soil-structure interactions and saturated porous media. The constitutive model captures particular features of clay behaviour, such as the prediction of strain rate dependence, small-strain stiffness degradation, the development of residual strength at very large shear strains and stress anisotropy. The effects of these features on the behaviour of two important geotechnical problems – including pipe-seabed interaction under lateral motion and dynamically installed anchors – are specifically investigated using two advanced finite deformation schemes: one based on the Arbitrary Lagrangian Eulerian (ALE) method and another on the Particle Finite Element Method (PFEM). The study illustrates the robustness of the proposed integration scheme and successful application of the soil model, indicating that the use of such complex soil models may be useful for realistic analyses of geotechnical problems.